Activity Test of N-Hexane Fraction of Takokak Fruit ( Solanum torvum Swartz ) Using Glucose Tolerance Test Method Per Oral (OGTT) in Test Animals White Rats (Rattus norvegicus) - Ahlan Sangkal; Rahmat Ismail; Febrianika Ayu Kusumaningtyas (International Journal of Public Health, 2024)
Takokak fruit contains bioactive compounds that can be used as antidiabetics. This study aims to identify bioactive compounds of ethanol extract of takokak fruit and antidiabetic test of n-Hexane fraction. The method used to obtain the extract is maceration using ethanol . Antidiabetic testing is carried out through in vivo testing with the Oral Glucose Tolerance Test (OGTT) method on white rats. Secondary metabolites are compounds contained in taakokak fruit that are identified as flavonoids, saponins, tannins, steroids and terpenoids . The results of the antidiabetic test showed that the n-Hexane fraction with glibencamide as a comparator has the ability as an antidiabetic in terms of the amount of difference in blood glucose levels in the test animal group from T 30 to T 120 . The average decrease in blood glucose levels in the negative control group (Na-CMC) was 108.67 mg/dL, the positive control group ( glibencamide ) 174.67 mg/dL, the 5% concentration fraction group 35.33 mg/dL, the 10% concentration fraction group 30.67 mg/dL, the 20% concentration fraction group 47.67 mg/dL.